1999
DOI: 10.1164/ajrccm.160.3.9809088
|View full text |Cite
|
Sign up to set email alerts
|

Elastosis and Fragmentation of Fibers of the Elastic System in Fatal Asthma

Abstract: Fibers of the elastic system (FES) are important in regulating airway patency and lung elastic recoil. Their possible role in modulating bronchoconstriction is not fully understood. Chronic inflammation and mechanical stretching present in asthma could lead to conformational alterations in the FES, participating in the mechanism of airway remodeling observed in this disease. In airway mucosa, two layers of FES are discernible: one superficial network, attached to the basement membrane, and a deeper network, ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
4
20

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(108 citation statements)
references
References 24 publications
8
76
4
20
Order By: Relevance
“…This is supported by in vitro studies showing increased responsiveness of human ASM after treatment with collagenase [131]. Loss of elastin may contribute to altered airway mechanics in asthma, possibly increasing deformability, with a tendency towards increased airway narrowing [63,65]. Thus, in some asthma cases the airways could be more collapsible, which will increase the tendency for airway closure.…”
Section: Airway Wall Collapsementioning
confidence: 87%
See 1 more Smart Citation
“…This is supported by in vitro studies showing increased responsiveness of human ASM after treatment with collagenase [131]. Loss of elastin may contribute to altered airway mechanics in asthma, possibly increasing deformability, with a tendency towards increased airway narrowing [63,65]. Thus, in some asthma cases the airways could be more collapsible, which will increase the tendency for airway closure.…”
Section: Airway Wall Collapsementioning
confidence: 87%
“…JAMES AND S. WENZEL I, III and IV [51][52][53][54]; decorin [55,56]; laminin [57,58]; tenascin [53,59,60]; versican [55,56,59]; biglycan [56,59,61]; perlecan [56,61]; hyaluranon [50,62]; and decreased lumican [55]. Reductions in elastin have been observed in a number of studies [63][64][65]. Increased collagen in the airway submucosa has also been observed in occupational asthma [66].…”
Section: Airway Remodelling In Airway Diseasesmentioning
confidence: 98%
“…Parallel observations have been made in the airways in severe asthma. MAUAD et al [28] performed morphometric studies on the central airways of subjects with fatal asthma, and found fragmentation of elastic fibres and a reduction in the content of elastic fibres in the subepithelial portion of the airway wall. In a subsequent study of fatal asthma, MAUAD et al [29] reported a reduction in the content of elastic fibres in the adventitial layer of the small airways, although they also noted a reduction in alveolar attachments to the small airways but without any evidence of changes in the elastic fibres elsewhere in the alveoli.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies are limited, distal lung parenchyma or alveolar tissue appears to be nearly devoid of fibrosis. Rather, data suggest abnormal loss of ECM in the alveolar interstitium adjacent to small airways in the distal lung tissue of individuals with fatal asthma (7,8). The cellular mecha-nisms of such contrasting matrix patterns in proximal airways versus distal lung tissue of individuals with asthma remain to be determined.…”
mentioning
confidence: 99%